Effectiveness of Health Promotion Program on Nurses’ Knowledge about Preventing Transmission of Communicable disease at Primary Health Care Centers in Al -Amara City - Tahssein Ali Hussein; Raad Kareem Fraaj (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Promoting and sustaining the knowledge of nurses in primary health care centers aboutpreventing transmission of communicable diseases intended to enable the nurse to develop health trendsin people, building healthy behavior, and enable the people to understand health messages to their familiesabout preventing the spread of communicable diseases.Objective: The study aim to evaluate the nurses’ knowledge about preventing transmission of Communicabledisease at Primary Health Care Centers, and to construction of educational program.Methodology: A quasi-experimental design has been carried out from (19) Primary Health Care Centersstarted from the 17th, November 2019 to 12th, April 2021. Select purposive sample comprised of 50 nursesis divided into two groups equally, study group were exposed to the nursing educational program, andcontrol group. Constructed the study instrument by researcher. Questionnaire consisted of (56) questions toevaluate the nurses’ knowledge about preventing transmission of Communicable diseases. The validity ofthe instrument obtained by 15 experts panel while reliability of instrument is determined using test and retestapproach. The analysis of data by application of description statistic (frequency, percentage, arithmeticmean and standard deviations) and inferential statistical (ANOVA, t-test and chi-square test)Results: The study reveal that the majority of nurses had deficit level of knowledge of evaluation at pre -testwhile control group were moderate level of knowledge about preventing transmission of Communicabledisease in Health promotion and Immunization units, while for post-test1,post-test2 presented improve instudy group for knowledge.